Let's make bread! : a comic book cookbook - Forkish, Ken (Ten Speed Graphic, an imprint of Ten Speed Press, 2024)
"An accessible and easy-to-follow comic book cookbook for the home baker, with key breadmaking steps and tips, guidelines for starting and maintaining a sourdough starter, recipes for classic loaves, and more--from the author of Flour, Water, Salt, Yeast."--